Classical Coulomb Energies JL (ρ) and JNL (ρ) of an Atomic Charge Distribution Studies with Partitioned Charge Density Function - Dutta, Mala (Asian Journal of Chemistry, 2010)
Density functional (DF) theory provides a methodology to study atomic and molecular systems in terms of the electron density function ρ(r) instead of the many-particle wave function Ψ(r). The Pacios density function has been used to calculate the JL(ρ) and JNL(ρ) as classical coulomb energies under various models. The results obtained are in good agreement with the Hartree-Fock estimates.